Mental Health Disparities Among Homosexual Men and Minorities: A Systematic Review - Muhammad Hadi Malik; Shahid Iqbal; Muhammad Noman; Zouina Sarfraz; Azza Sarfraz; Shabbir Mustafa (American Journal of Men's Health, 2023)
Mental health disparities in sexual minorities, particularly homosexual and bisexual men, are a significant public health concern. This study examines six key themes: general psychiatric issues, health services, minority stress, trauma and PTSD, substance and drug misuse, and suicidal ideation. The aim is to provide a comprehensive synthesis of the evidence, identify potential intervention and prevention strategies, and address knowledge gaps in understanding the unique experiences of homosexual and bisexual men. Reported as per the PRISMA Statement 2020 guidelines, PubMed, PsycINFO, Web of Science, and Scopus were searched until February 15, 2023, with no language restrictions. A combination of the following keywords and MeSH terms was used: homosexual, bisexual, gay, men who have sex with men, mental health, psychiatric disorders, health disparities, sexual minorities, anxiety, depression, minority, stress, trauma, substance, drug misuse, and/or suicidality. Out of 1,971 studies located through database searching, 28 were included in this study pooling a total of 199,082 participants from the United States, the United Kingdom, Australia, China, Canada, Germany, the Netherlands, Israel, Switzerland, and Russia. Thematic findings of all the studies were tabulated and thereby synthesized. Addressing mental health disparities in gay, bisexual men, and sexual minorities requires evidence-based, comprehensive approaches, culturally competent care, accessible services, targeted prevention strategies, community-based support, public awareness, routine screenings, and research collaboration. This inclusive, research-informed approach can effectively reduce mental health issues and enable optimal well-being in these populations.